ANALISIS BIAYA MANFAAT PROGRAM PEMBANGUNAN FOOD ESTATE DALAM PERSPEKTIF PERENCANAAN WILAYAH : STUDI KASUS PROVINSI KALIMANTAN BARAT - Asti Asti; Dominicus Savio Priyarsono; Sahara Sahara (Jurnal Agribisnis Indonesia, 2016)
Food Estate Development Program is an investment project on food cropsubsector in the form of business activities with large-scale cultivation (> 25 ha), especially rice commodities. The present study aims to analyze economic feasibility of Food Estate Development Program. The methode used to answer the research was NPV, IRR, BCR, Pay Back Period and sensitivity analysis. The results show that the NPV is positive amounted 153.761,83 billions rupiah, IRR of 63%, BCR of 1,25, Pay Back Period of 8 years and the sensitivity analysis of sensitive to changes in prices of inputs and outputs. From the above considerations investment criteria, indicates that program is economically feasible.